A Performance Evaluation of Three-Phase Induction Electric Motors between 1945 and 2020 - de Souza, Danilo Ferreira (2022)
In the late 19th century, the three-phase induction motor was the central element of productivity increase in the second industrial revolution in Europe and the United States. Currently, it is the main load on electrical systems in global terms, reaching approximately 70% of electrical energy consumption in the industrial sector worldwide. During the 20th century, electric motors underwent intense technological innovations that enabled significant performance gains. Thus, this work analyses the performance changes in squirrel-cage rotor three-phase induction electric motors (SCIMs) with mechanical powers of 3.7 kW, 37 kW, and 150 kW and speed ranges corresponding to two poles and eight poles, connected to a low voltage at a frequency of 60 Hz and tested between 1945 and 2020. The study confirms accumulated performance gains of above 10% in some cases. Insulating materials for electrical conductors have gone through several generations (cotton, silk, and currently, varnish). Improvements to the housing for cooling, the bearings, the quality of active materials, and the design were the elements that enabled the high gains in performance. The first commercial two-pole SCIM with a shaft power of 4.4 kW was marketed in 1891, with a weight/power ratio of 86 kg/kW, and until the 2000s, this value gradually decreased, eventually reaching 4.8 kg/kW. Between 2000 and 2020, this ratio showed a reversed trend based on improvements in the performance of SCIMs. More active materials were used, causing the weight/power ratio to reach 8.6 kg/kW. The MEPS (minimum energy performance standards) of SCIMs had an essential role in the performance gain over the last three decades. Data collection was via tests at the Electrical Machines Laboratory of the Institute of Energy and Environment of the University of São Paulo. The laboratory has a history of tests on electrical equipment dating from 1911.